Significant effects of cementitious materials on strength gain properties of concrete with partial replacement of fine aggregate by quarry dust - Suganya, S; Rajkumar, V (International Journal of Engineering and Technology, 2018)
Concrete incorporates large amount of natural resource as aggregates with cement and water. Cement production consumes huge energy and causes about 7% of total greenhouse gas emission in the world. It has been strived to provide better quality in concrete using waste by-products from industries so that natural resources are used in an efficient manner and thereby the environment is protected from waste deposits. Hence, mineral admixtures like fly ash and micro silica can be used to overcome these issues. The demand for river sand is getting increased day by day, which affects its constant supply. Under these circumstances use of quarry dust becomes inevitable. The usage of fly ash in the concrete leads to strength gain only at later stages. In order to obtain strength during the early stage, micro silica is added as a partial replacement of cement. The properties of fly ash, micro silica and quarry dust were studied. Fly ash (0-40%) and micro silica (0-15%) are used as a partial replacement for cement and quarry dust (50%) as that for river sand by mass. Mechanical properties of the concrete containing hybrid mineral admixtures and quarry dust are studied systematically.Â Â